Analiza Stateczności Cienkościennej Powłoki Walcowej Poddanej Rozciąganiu w Stanie Plastycznym - Marciniak, Z. (Engineering Transactions, 1958)
The possibility of the appearance of local neck or buckling during plastic deformation is discussed for a thick-walled cylindrical shell subjected to the action of axial force and internal pressure, using the real strain hardening curve given in the form of a diagram. The form of stability loss depends on the phenomenon of strain hardening during the deformation process. A method is given for determining the value of plastic strain for which stability loss occurs, using the strain-hardening curve in the Q-6H coordinate system. By way of example, diagrams are presented illustrating the possibility of stability loss during the tension of mild steel shells.